MODEL PENGENDALIAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS - Juwita, Lisavina; Febrina, Wiwit (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
According to the International Diabetes Federation (IDF) there are 382 million people living with diabetes in the world by 2013. It is estimated that of the 382 million people, 175 million of whom remain undiagnosed, so the danger of developing progressive complications unwittingly and without prevention. Complications from diabetes can be prevented or delayed by keeping blood sugar levels are in the normal category so that metabolism can be well controlled. Blood sugar levels can be maintained by a healthy lifestyle. The purpose of this study was to determine the control of blood sugar levels by making healthy lifestyle in patients with diabetes mellitus type II in London in 2017: a grounded theory study. Participants in the study of 18 people. Intake of participants in this study begins with purposive sampling. The results showed the main concept of grounded theory is